2014
DOI: 10.1155/2014/528084
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Staphylococcal Ocular Infections of Food Producing Animals in Nsukka Southeast, Nigeria

Abstract: Staphylococcal ocular infections of food animals have been somewhat under diagnosed probably due to the ubiquitous nature of staphylococcal organisms. This study was undertaken to determine the occurrence of staphylococcal ocular infections of food producing animals in Nsukka Southeast, Nigeria, and to determine the antibiogram of the isolated staphylococci. A total of 5,635 food producing animals were externally examined for signs of clinical ocular conditions. Animals that showed clinical eye lesions were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Being a normal flora in the environment, or skin, and mucous membranes of animals and humans, S. aureus isolates could acquire antibiotics resistance from other organisms, while the misuse of antimicrobial medicines accelerates this phenomenon (Udegbunam et al, 2014). Our study showed a diverse resistance profile of these isolates and a great occurrence of the resistance to 14 antimicrobial agents, which probably was a result of the frequent use of these antibiotics.…”
Section: Classmentioning
confidence: 62%
See 1 more Smart Citation
“…Being a normal flora in the environment, or skin, and mucous membranes of animals and humans, S. aureus isolates could acquire antibiotics resistance from other organisms, while the misuse of antimicrobial medicines accelerates this phenomenon (Udegbunam et al, 2014). Our study showed a diverse resistance profile of these isolates and a great occurrence of the resistance to 14 antimicrobial agents, which probably was a result of the frequent use of these antibiotics.…”
Section: Classmentioning
confidence: 62%
“…Susceptibility to 14 antimicrobial agents for all 93 isolates was performed by the disc diffusion procedure recommended by the Clinical and Laboratory Standards Inst. guidelines ( [CLSI] Clinical and Laboratory Standards Inst, 2012) and other reported references (Jackson et al, 2013;Udegbunam, Udegbunam, & Anyanwu, 2014). Escherichia coli ATCC 25922 and S. aureus ATCC 25923 were used as a quality control strains.…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…[ 40 ] but lower than Lee [ 28 ] and Udegbunam et al . [ 41 ], who reported 89.4% and 100%, respectively. There is a high MRSA susceptibility to (aminoglycoside) gentamicin and the fluoroquinolones (NOR) tested in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The observed high MRSA susceptibility to aminoglycoside (gentamicin) and fluoroquinolones (NOR) in this study supports some previous reports [ 43 , 44 ]. In addition, the high rate of susceptibility may not be unconnected to the fact that fluoroquinolones are not commonly used in treating food animals, except for poultry and their usage in humans [ 41 ]. Thus, the susceptibility of MRSA to non-β-lactam antibiotics may provide a window opportunity for the recommendation of these drugs for the empirical treatment of MRSA strains, thereby reducing sole reliance on the usage of β-lactam antibiotics for the treatment of mecA encoding bacteria.…”
Section: Discussionmentioning
confidence: 99%